Psychometric Properties and Correlates of Precarious Manhood Beliefs in 62 Nations. (April 2021) - Bosson, Jennifer K.; Jurek, Paweł; Vandello, Joseph A.; Kosakowska-Berezecka, Natasza; Olech, Michał; Besta, Tomasz; Bender, Michael; Hoorens, Vera; Becker, Maja; Timur Sevincer, A.; Best, Deborah L.; Safdar, Saba; et al.
Precarious manhood beliefs portray manhood, relative to womanhood, as a social status that is hard to earn, easy to lose, and proven via public action. Here, we present cross-cultural data on a brief measure of precarious manhood beliefs (the Precarious Manhood Beliefs scale [PMB]) that covaries meaningfully with other cross-culturally validated gender ideologies and with country-level indices of gender equality and human development. Using data from university samples in 62 countries across 13 world regions ( N = 33, 417), we demonstrate: (1) the psychometric isomorphism of the PMB (i.e., its comparability in meaning and statistical properties across the individual and country levels); (2) the PMB's distinctness from, and associations with, ambivalent sexism and ambivalence toward men; and (3) associations of the PMB with nation-level gender equality and human development. Findings are discussed in terms of their statistical and theoretical implications for understanding widely-held beliefs about the precariousness of the male gender role.